IMPLEMENTATION OF SOCIAL WORK SANCTIONS AS A SUBSTITUTE TO PUNISHMENT UNDER ONE YEAR PRISON AGAINST THE CRIMINAL ACTION OF IT - Firman Wijaya (Awang Long Law Review, 2022)
The social work crime contains elements of rehabilitation, re-education and resocialization. During the execution of the crime, prisoners will be fostered and guided in terms of the formation of attitudes and behavior. The development of the convict's work and personality is always monitored and monitored by community officials. Prisoners will be guided to be able to behave well and actively participate in development. The problem is how is the sentence below one year in prison for the perpetrators of the ITE crime in Decision Number 1636/Pid.Sus/2020/PN.Jkt.Brt? The method used is normative juridical. The conclusion is that they do not agree with the Judge's Decision in Decision Number 1636/Pid.Sus/2020/PN.Jkt.Brt., because the Defendant may be subject to social work sanctions as a substitute for a sentence of less than one years in prison. In principle, social work crime is an alternative to short-term deprivation of liberty. Social work crime is a type of crime that will be imposed on perpetrators of crimes that are not too serious. Starting from the various privileges of the social work crime, it is clear that even though it is a crime, this social work crime is not forced labor. Social work crime is a form of crime that is loaded with the content of protecting human rights.